On the generalizations of polynomial inequalities in the complex domain - P. N. Kumar (Հայաստանի ԳԱԱ)
In this paper we establish some generalizations of Bernstcin-type inequalities for polynomials having zeros in the closed interior or closed exterior of a circle of radius |z|=K.
Keywords: Science; Mathematics